Is the Social Safety Net a Long-Term Investment? Large-Scale Evidence From the Food Stamps Program - Bailey, Martha J; Hoynes, Hilary; Rossin-Slater, Maya; Walker, Reed (Review of Economic Studies, 2024)
We use novel, large-scale data on 17.5 million Americans to study how a policy-driven increase in economic resources affects children's long-term outcomes. Using the 2000 Census and 2001-13 American Community Survey linked to the Social Security Administration's NUMIDENT, we leverage the county-level rollout of the Food Stamps program between 1961 and 1975. We find that children with access to greater economic resources before age five have better outcomes as adults. The treatment-on-the-treated effects show a 6% of a standard deviation improvement in human capital, 3% of a standard deviation increase in economic self-sufficiency, 8% of a standard deviation increase in the quality of neighbourhood of residence, a 1.2-year increase in life expectancy, and a 0.5 percentage-point decrease in likelihood of being incarcerated. These estimates suggest that Food Stamps' transfer of resources to families is a highly cost-effective investment in young children, yielding a marginal value of public funds of approximately sixty-two.